The Role of Riau Pavilion in Increasing Tourist Visits to Riau Region - Pradini, Gagih; Agustiani, Fitri; Sondang, Devitha; Resmi, Prasiwi Citra; Kastuti, Indriati (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Anjungan Riau plays a significant role in enhancing tourist visits to Riau. As a promotional platform, it raises awareness and interest among both local residents and international tourists regarding Riau's tourism potential. By organizing exhibitions, events, and various marketing strategies, Anjungan Riau effectively showcases the diverse range of attractions and cultural activities in the region. It also serves as a reliable source of comprehensive information for tourists, offering details on tourist spots, local customs, and unique experiences available in Riau. In addition to promoting tourism, Anjungan Riau contributes to the empowerment of the local economy by providing a marketplace for locally-produced crafts, traditional foods, and other goods. This not only boosts the income of local communities but also highlights the rich cultural heritage of Riau. Furthermore, Anjungan Riau fosters collaboration and establishes networks within the tourism industry, forging partnerships with travel agents, hotels, restaurants, and other relevant entities. Such collaborations expand the reach and further enhance the allure of Riau as a tourist destination. In conclusion, Anjungan Riau plays a crucial role in increasing tourist visits to Riau by promoting its attractions, providing essential information, empowering the local economy, and fostering collaboration between stakeholders.